Comparison of TLD calibration methods for 192Ir dosimetry. (7th January 2013) - Haworth, Annette; Butler, Duncan J.; Wilfert, Lisa; Ebert, Martin A.; Todd, Stephen P.; Hayton, Anna J.M.; Kron, Tomas
Abstract : For the purpose of dose measurement using a high‐dose rate   192 Ir source, four methods of thermoluminescent dosimeter (TLD) calibration were investigated. Three of the four calibration methods used the   192 Ir source. Dwell times were calculated to deliver 1 Gy to the TLDs irradiated either in air or water. Dwell time calculations were confirmed by direct measurement using an ionization chamber. The fourth method of calibration used 6 MV photons from a medical linear accelerator, and an energy correction factor was applied to account for the difference in sensitivity of the TLDs in   192 Ir and 6 M V. The results of the four TLD calibration methods are presented in terms of the results of a brachytherapy audit where seven Australian centers irradiated three sets of TLDs in a water phantom. The results were in agreement within estimated uncertainties when the TLDs were calibrated with the   192 Ir source. Calibrating TLDs in a phantom similar to that used for the audit proved to be the most practical method and provided the greatest confidence in measured dose. When calibrated using 6 MV photons, the TLD results were consistently higher than the   192 Ir − calibrated TLDs, suggesting this method does not fully correct for the response of the TLDs when irradiated in the audit phantom. PACS number: 87